Statistical Approaches With Emphasis on Design of Experiments Applied to Chemical Processes - Silva, Valter (IntechOpen, 2018)
Optimized operating conditions for complex systems can be attained by using advanced combinations of numerical and statistical methodologies. One of the most efficient and straightforward solutions relies on the application of statistical methods with an emphasis on the design of experiments (DoEs). Throughout the book, the design and analysis of experiments are conducted involving several approaches, namely, Taguchi, response surface methods, statistical correlations, or even fractional factorial and model-based evolutionary operation designs. This book not only presents a theoretical overview about the different approaches but also contains material that covers the use of the experimental analysis applied to several chemical processes. Some chapters highlight the use of software products to assist experimenters in both the design and analysis stages. It helps graduate students, teachers, researchers, and other professionals who are interested in chemical process optimization and also provides a good basis of theoretical knowledge and valuable insights into the technical details of these tools as well as explains common pitfalls to avoid. The world's leading pharmaceutical companies and local governments are trying to achieve their eradication.